Metaphysical Causation - Wilson, Alastair (Noûs (Bloomington, Indiana), 2018)
There is a systematic and suggestive analogy between grounding and causation. In my view, this analogy is no coincidence. Grounding and causation are alike because grounding is a type of causation: metaphysical causation. In this paper I defend the identification of grounding with metaphysical causation, drawing on the causation literature to explore systematic connections between grounding and metaphysical dependence counterfactuals, and I outline a non‐reductive counterfactual theory of grounding along interventionist lines.